Rhoifolin Ameliorates Osteoarthritis via Regulating Autophagy - Jiyuan Yan; Bowei Ni; Gaohong Sheng; Yingchi Zhang; Yifan Xiao; Yongzhuang Ma; Hao Li; Hua Wu; Chang Tu (Frontiers Media S.A., 2021)
Osteoarthritis (OA) is a common age-related joint disease. Its development has been generally thought to be associated with inflammation and autophagy. Rhoifolin (ROF), a flavanone extracted from Rhus succedanea, has exhibited prominent anti-oxidative and anti-inflammatory properties in several diseases. However the exact role of ROF in OA remains unclear. Here, we investigated the therapeutic effects as well as the underlying mechanism of ROF on rat OA. Our results indicated that ROF could significantly alleviate the IL-1β-induced inflammatory responses, cartilage degradation, and autophagy downregulation in rat chondrocytes. Moreover, administration of autophagy inhibitor 3-methyladenine (3-MA) could reverse the anti-inflammatory and anti-cartilage degradation effects of ROF. Furthermore, P38/JNK and PI3K/AKT/mTOR signal pathways were involved in the protective effects of ROF. In vivo, intra-articular injection of ROF could notably ameliorate the cartilage damage in rat OA model. In conclusion, our work elucidated that ROF ameliorated rat OA via regulating autophagy, indicating the potential role of ROF in OA therapy.